Pengembangan Perangkat Pembelajaran Berbasis Inkuiri Terbimbing Melalui Pendekatan Keterampilan Proses Sains Untuk Meningkatkan Hasil Belajar Fisika Peserta Didik - Yuyun Parwati; Gunawan Gunawan; Muhammad Zuhdi; Kosim Kosim (Indonesian, 2020)
This study aims to develop guided inquiry physics high school physics learning tools through an appropriate science process skill approach. The learning kit was designed using the 4-D model, followed by implementing the assessment with fellow students. Data collection was done through device validation. Data analysis was carried out using qualitative and quantitative descriptive. The results obtained indicate the device's validity, including syllabus, lesson plans, LKPD, and learning achievement test instruments using the CVR and CVI categorized as very valid. Reliability of learning tools that implement the syllabus, lesson plans, LKPD, and test instruments using the Percentage Agreement (PA). The learning tools developed are reliable in terms of the achievement of learning indicators that have a PA value of more than 75%. Students' response is positive towards the development of learning tools. Based on these results, it can be concluded that the guided inquiry-based learning device through the science process skill approach that was developed is feasible to be used in learning activities to improve students' physics learning outcomes.